CIRCULAR SUPPLY CHAIN MANAGEMENT: CONTENT ANALYSIS WITH SPECIFIC DRIVERS AND BARRIERS - Upadhyay, Anjali; Shukla, Apratul Chandra (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The entire process of producing, distributing, and delivering goods and services to consumers in the supply chain has a significant impact on the environment. The transition towards Circular Supply Chain Management (CSCM) is imperative for addressing contemporary sustainability challenges. This study attempts a systematic exploration of the key barriers and drivers influencing the adoption of circular practices within supply chains by using content analysis and a systematic literature review. This paper highlighted the importance of CSCM adoption. The outcome of the study is relevant as it gives a framework of barriers and drivers for the CSCM implementation by a force field analysis. Various critical factors are assumed to define hypotheses as the basis of further research. This review has great significance for CSCM practitioners, academicians, managers, and policymakers. By recognizing the barriers and the drivers, organizations can embark on a transformative journey toward circular practices in their supply chains.